Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and strong plasticity matching and preparation method thereof
By optimizing the chemical composition and phase composition of Fe-Cr-Ni-Co-Ti-Al high-entropy alloys, the trade-off problem between strength and corrosion resistance of high-entropy alloys is solved, and high mechanical properties and good resistance are achieved. Corrosion performance matching.
Patent Information
- Application Number
- CN202310415940.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-04-18
AI Technical Summary
High-entropy alloys have a trade-off between strength and corrosion resistance, making it difficult to achieve high mechanical properties and good corrosion resistance at the same time.
By optimizing the chemical composition of the Fe-Cr-Ni-Co-Ti-Al high-entropy alloy, adding an appropriate amount of Al element, changing the phase composition of the alloy, from FCC+Sigma to FCC+BCC to FCC+BCC+Sigma combination , improve the yield strength and compressive strain resistance of the alloy, and at the same time improve its corrosion resistance.
It achieves high yield strength (up to 1315.3MPa), ultimate strength (over 3000MPa) and high compressive strain (over 45%) of high-entropy alloys, while significantly improving its corrosion resistance, with a corrosion current density lower than that of 304 super stainless steel. , the self-corrosion potential and pitting corrosion potential are both higher than 304 super stainless steel.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to a Fe-Cr-Ni-Co-Ti-Al series high entropy alloy with high corrosion resistance and strong plasticity matching, and a preparation method thereof. Background Art
[0002] High-strength metal materials with appropriate ductility have always been the first choice for transportation, spacecraft and other major engineering applications. In addition to mechanical properties, good corrosion resistance is also crucial for engineering materials to prevent service failure in harsh environments. Therefore, the exploration of corrosion-resistant metal materials with excellent mechanical properties has developed into one of the most important research and development hotspots in the field of materials in recent years.
[0003] High entropy alloys (HEAs), also known as multi-principal element alloys (MPEAs), are a new type of material that breaks through the traditional alloy design mode based on a single principal element. Due to the four core effects, HEAs not only greatly expand the design range of alloys, but also exhibit many remarkable properties, such as high strength, good toughness, excellent wear resistance, radiation resistance, corrosion resistance, and oxidation resistance. Therefore, the concept of HEA provides the possibility of achieving the mechanical properties-corrosion resistance synergy of metallic materials. Unfortunately, some recent studies have shown that for most HEAs, there seems to be a trade-off between strength and corrosion resistance. In fact, it is not surprising that there is such a dilemma in HEAs. Similar to traditional alloys, some strengthening mechanisms are also applicable to HEAs, such as second phase strengthening and dislocation strengthening, which may sometimes lead to the deterioration of corrosion resistance. For example, according to the Hall-Petch relationship, grain refinement can provide higher strength, but high-density grain boundaries accelerate the segregation of alloying elements due to higher interface energy, which can easily lead to electrochemical corrosion. Micro-galvanic corrosion generally occurs between the matrix phase and the precipitate phase, which further promotes the dissolution of the anodic phase and even causes localized corrosion. In addition, it has also been reported that dislocation strengthening based on the pre-deformation process will bring a certain number of defects to the alloy matrix, resulting in a decrease in the corrosion performance of HEA. Therefore, it is imperative to resolve the contradiction between the mechanical and corrosion properties of HEA. Summary of the invention
[0004] The purpose of the present invention is to provide a Fe-Cr-Ni-Co-Ti-Al series high entropy alloy with high corrosion resistance and strong plasticity matching and a preparation method thereof, which can achieve the improvement of corrosion resistance of the high entropy alloy and the matching of strength and toughness.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and strong plasticity matching, characterized in that the chemical formula of the high entropy alloy is calculated by atomic percentage: (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x , where 0≤x≤7.5.
[0007] In the chemical expression of the high entropy alloy, the x value is preferably: 2.5≤x≤7.5.
[0008] The phase composition of the high entropy alloy changes with the increase of Al content. When the Al content is 0 (x=0), the phase composition is FCC+Sigma; in the process of Al content increasing from 0 to 3at.%, the Sigma phase gradually transforms into the BCC phase; when the Al content reaches 3at.% (x=3), the Sigma phase is completely transformed into BCC, and the phase composition is FCC+BCC; when the Al content increases from 3at.% to 7at.% (3<x<7), the phase composition is FCC+BCC; when the Al content is 7at.%, the Sigma phase appears, and the phase composition is FCC+BCC+Sigma; when the Al content gradually increases from 7at.% (7<x≤7.5), the phase composition is FCC+BCC+Sigma, but the Sigma phase gradually increases and the FCC gradually decreases; when 5≤x≤7.5, the B2 phase appears.
[0009] The composition of multiple phases of the high-entropy alloy enables the high-entropy alloy to have a yield strength of up to 1315.3 MPa and an ultimate strength of more than 3000 MPa. At the same time, the compressive strain of the high-entropy alloy exceeds 45% and does not even break.
[0010] The corrosion current density of the high entropy alloy ranges from 0.034 to 0.118 μA / cm 2 , are less than 304 super stainless steel; self-corrosion potential -131.5~-114mV SCE , pitting potential range 451.2~953.4mV SCE , passivation range 582.7~1067.4mV SCE , which are higher than 304 super stainless steel, proving that the high entropy alloy of the present invention has excellent corrosion resistance.
[0011] The preparation method of the Fe-Cr-Ni-Co-Ti-Al high-entropy alloy with high corrosion resistance and matched strength and plasticity is as follows: the method adopts a vacuum arc melting method, weighs each element raw material according to the chemical composition of the high-entropy alloy, and turns it over more than 5 times and then naturally solidifies to obtain an alloy ingot.
[0012] The design mechanism of the present invention is as follows:
[0013] Reasonable phase selection and guarantee of corrosion resistant element content are effective ways to achieve matching of mechanical properties and corrosion resistance of high entropy alloys. 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x As the target material, the main design ideas of high entropy alloy are as follows. First, high content of Cr and a small amount of added Ti can provide improvements in passive film stability and local corrosion resistance; second, changes in the content of Al element addition will cause changes in the phase composition in the alloy. This diversity of phase adjustment provides an opportunity to match mechanical properties with corrosion resistance.
[0014] The advantages and beneficial effects of the present invention are as follows:
[0015] 1. The high entropy alloy described in the present invention can achieve a match between corrosion resistance and strength and plasticity.
[0016] 2. The phase composition of the high entropy alloy of the present invention can be freely selected from the combination of FCC+Sigma, FCC+BCC, and FCC+BCC+Sigma. The composition of different phases makes the yield strength of the high entropy alloy of the present invention reach up to 1315.3MPa, and the ultimate strength exceeds 3000MPa. At the same time, the compressive strain of all high entropy alloys exceeds 45% and even does not break. At the same time, the corrosion current density of the high entropy alloy of the present invention is in the range of 0.034 to 0.118μA / cm 2 , are all less than 304 super stainless steel, self-corrosion potential -131.5~-114mV SCE , pitting potential range 451.2~953.4mV SCE , passivation range 582.7~1067.4mV SCE , which are higher than 304 super stainless steel, proving that the high entropy alloy of the present invention has excellent corrosion resistance.
[0017] 3. The method for preparing the Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and matched strength and plasticity described in the present invention can be achieved by simple vacuum arc melting, and the operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 For the high entropy alloy (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100 -x Al xXRD spectrum of .
[0019] Figure 2 For the high entropy alloy (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100 -x Al x EBSD phase diagram; wherein: (a)-(f) are EBSD tests of Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 1 respectively; (g) is the corresponding volume fractions of FCC, BCC and Sigma in each embodiment and comparative example.
[0020] Figure 3 For the high entropy alloy (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100 -x Al x SEM-BSE images; wherein: (a) Example 1: x=0, (b) Example 2: x=3, (c) Example 3: x=5, (d) Example 4: x=6, (e) Example 5: x=7, (f) Comparative Example 6: x=8, (g), (h) and (i) are local high-magnification images of (d), (e) and (f), respectively.
[0021] Figure 4 For each embodiment and comparative example (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x EDS spectrum of high entropy alloy.
[0022] Figure 5 Characterization of the alloy of Example 5 of the present invention; including: (a) dark field TEM image, (b) corresponding SAED pattern, (c) HAADF image, (d) EDS diagram, and (e) composition overview of each phase.
[0023] Figure 6 For the examples and comparative examples (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x Room temperature properties of high entropy alloys; (a) compressive stress-strain curve; (b) relationship between yield strength and Al content (x).
[0024] Figure 7For the examples and comparative examples (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x Potential-dynamic polarization curves of high entropy alloy in 3.5wt.% NaCl solution.
[0025] Figure 8 For the examples and comparative examples (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x High entropy alloys at a current density of 1 mA cm -2 The corrosion morphology after the potential polarization test; wherein: (a) Example 1; (b) Example 2; (c) Comparative Example 1.
[0026] Fig. 9 For the examples and comparative examples (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x EIS response of a high entropy alloy in 3.5 wt.% NaCl solution at room temperature; where: (a) Nyquist plot; (b) Bode plot; the inset of (a) represents the equivalent circuit. DETAILED DESCRIPTION
[0027] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.
[0028] The high entropy alloys of the embodiments of the present invention and the comparative examples are all obtained by vacuum arc melting. The chemical compositions of the cast alloys of the specific embodiments and the comparative examples are shown in Table 1.
[0029] Table 1 Chemical composition of high entropy alloys of Examples and Comparative Examples (at.%)
[0030] Example variable x Composition expression (at.%) Example 1 0 <![CDATA[Fe 33 Cr 36 If 15 Co 15 Ti1]]> Example 2 3 <h2 style=";text-align:left;direction:ltr"><![CDATA[(Fe <h2 style=";text-align:left;direction:ltr"> 33 <h2 style=";text-align:left;direction:ltr"> Cr<h2 style=";text-align:left;direction:ltr"> 36 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 15 <h2 style=";text-align:left;direction:ltr"> Co<h2 style=";text-align:left;direction:ltr"> 15 <h2 style=";text-align:left;direction:ltr"> Ti1)<h2 style=";text-align:left;direction:ltr"> 97 <h2 style=";text-align:left;direction:ltr"> Al3]]><h2 style=";text-align:left;direction:ltr"> Example 3 5 <![CDATA[(Fe 33 Cr 36 In 15 Co 15 If1) 95 Al5]]> Example 4 6 <![CDATA[(Fe 33 Cr 36 If 15 Co 15 Ti1) 94 Al6]]> Example 5 7 <h2 style=";text-align:left;direction:ltr"><![CDATA[(Fe <h2 style=";text-align:left;direction:ltr"> 33 <h2 style=";text-align:left;direction:ltr"> Cr<h2 style=";text-align:left;direction:ltr"> 36 <h2 style=";text-align:left;direction:ltr"> Ni<h2 style=";text-align:left;direction:ltr"> 15 <h2 style=";text-align:left;direction:ltr"> Co<h2 style=";text-align:left;direction:ltr"> 15 <h2 style=";text-align:left;direction:ltr"> Ti1)<h2 style=";text-align:left;direction:ltr"> 93 <h2 style=";text-align:left;direction:ltr"> Al7]]><h2 style=";text-align:left;direction:ltr"> Comparative Example 1 8 <![CDATA[(Fe 33 Cr 36 If 15 Co 15 Ti1) 92 Al8]]>
[0031] Figure 1The XRD patterns of the high entropy alloys of Examples 1-5 and Comparative Example 1 are shown. As shown in the figure, the four crystal structures (expressed as FCC, BCC, Sigma and B2) have obvious characteristics, and as the aluminum content increases, the phase structure changes. Obviously, FCC and Sigma phases are shown in the alloy of Example 1, but the alloy of Example 2 shows peaks of FCC and BCC phases, indicating that the introduction of Al can effectively inhibit the appearance of Sigma phase and lead to the formation of BCC structure. The alloys of Examples 2-4 (x=3, 5 and 6) show a conventional dual-phase microstructure of FCC+BCC phase. At the same time, as the Al content increases, the diffraction peak intensity of the BCC phase gradually increases, indicating an increase in the BCC phase (volume percentage). A very small amount of Sigma phase appears in the alloy of Example 5 (x=7), and the phase composition is FCC+BCC+Sigma; when x continues to increase, Sigma gradually increases and FCC gradually decreases. When x increases to 8 (Comparative Example 1 alloy), the FCC phase in the crystal structure is completely transformed into the Sigma phase, and the composition becomes the BCC+Sigma phase. In the alloys of Examples 3-5 and Comparative Example 1, a slight diffraction peak (100) can be detected near 2θ=30°, which indicates the presence of an ordered B2 phase.
[0032] In order to clearly observe the phase transformation and phase fraction, EBSD tests were performed on the high entropy alloys of Examples 1-5 and Comparative Example 1. Figure 2 As shown in Figure 1, it can be found that the alloy of Example 1 has a prominent dual-phase structure, in which there are 71% FCC phase and 29% Sigma phase. The appearance of the BCC structure is inductive, and its volume fraction increases with the addition of Al element, corresponding to Figure 1 The diffraction peak of BCC in the high entropy alloy of Example 2-5 is shown. In the high entropy alloy of Example 2-5, the FCC phase is located in the dendrite (DR) region, while the BCC phase is generated in the interdendritic (IR) region. In addition, an extremely rare Sigma phase (0.296 vol.%) exists in the alloy of Example 2, and when the atomic fraction of Al added is 7%, that is, in the alloy of Example 5, the Sigma phase appears again. For the alloy of Comparative Example 1, it shows a mixed structure of BCC phase (94.8 vol.%) and Sigma phase (5.05 vol.%). From Figure 2 (g) It can be seen that with the increase of Al content, the proportion (volume percentage) of FCC phase decreases to 0.14%, while the BCC phase increases to 94.8%. Figure 3BSE micrographs of the high entropy alloys of Examples 1-5 and Comparative Example 1 are shown. The alloy of Example 1 exhibits a typical dual-phase dendritic structure, and it can be inferred that the gray DR structure is the FCC phase, while the bright ID structure is the Sigma phase. In addition, with the introduction of Al, the high entropy alloy of the present invention also exhibits an obvious cast dendritic structure, and it can be inferred that the bright area is the FCC phase of the dendritic structure or the bulk Sigma phase. Figure 3 In b, dark regions (determined to be BCC phases) were detected, which is consistent with the XRD analysis ( Figure 1 ) are consistent. For the alloy of Example 3 (see Figure 3 c), the bright FCC phase evolves into a lath structure, which is identified as the Widmanstatten side plates, while the dark BCC phase constitutes the interlayer region. When the Al content is further increased, fewer plates exist in the alloys of Example 4 and Example 5 (see Figure 3 d and e), which eventually completely disappeared in the alloy of Comparative Example 1. In addition, it dominates as a dark BCC / B2 phase in the alloys of Example 4, Example 5 and Comparative Example 1. The FCC phase is mainly located and grows along the grain boundaries, and the proportion (volume percentage) of FCC decreases with the increase of Al element (at.%). Considering that the B2 phase is the structure of an ordered BCC phase, the corresponding EBSD micrographs still show a uniform structure (see Figure 2 be). A higher magnification image ( Figure 3 gi) shows randomly distributed, approximately spherical precipitates in the BCC matrix.
[0033] Figure 4 The element distribution of the high entropy alloys of Examples 1 to 5 and Comparative Example 1 detected by EDS is shown. For the high entropy alloy of Example 1 having an FCC+Sigma phase, Cr is enriched in the Sigma phase (>40at.%), while the Fe, Co, Ni and Ti elements in the FCC phase are higher than those in the Sigma phase. It is worth noting that the FCC phase also has a higher chromium content (31.80at.%), indicating that it may have good corrosion resistance. As for aluminum-containing alloys, the distribution of iron elements is relatively uniform, while nickel, cobalt and titanium elements are relatively abundant in the FCC phase. As powerful BCC stabilizers and Al and Cr forming elements, it can be seen that the BCC phase contains more Al and Cr elements than the FCC phase. Since the content of FCC phase in the comparative example 1 alloy is low (volume percentage), it is difficult to obtain its accurate content.
[0034] The detailed nanostructure of the alloy of Example 5 was characterized by TEM. Figure 5a shows the dark field (DF) of the alloy of Example 5. There are some large cubic nanoparticles and small nanoparticles randomly dispersed in the matrix. The SAED pattern along the
[001] zone axis ( Figure 5 b) shows that these nanoparticles are of B2 structure. Figure 5 cd shows the HAADF image and EDS spectrum of the nanostructure. It is obvious that Ni and Al elements are abundant in the B2 phase, while enrichment of Fe and Cr elements is observed in the BCC phase, and there is no segregation of Co element. In particular, Ti element is found to be dissolved in the B2 phase, and EDS line analysis ( Figure 5 e) have similar element distribution results.
[0035] Figure 6 a shows the curves of the alloys of Examples 1 to 5 of the present invention and Comparative Example 1 after compression tests at room temperature. The corresponding mechanical property parameters are shown in Table 2. When the Al element is introduced into the alloy, its mechanical properties are significantly improved. The yield strength, fracture strength and plastic strain of the high entropy alloy of Example 1 with FCC+Sigma dual phase are 615.06MPa, 2196.27MPa and 45.9%, respectively. Compared with the high entropy alloy of Example 1, it can be found that with the increase of Al content (x=3, Example 2), the yield strength changes from 615.06MPa to 579.81MPa, but the toughness is greatly improved. As Figure 6 As shown in (a), no fracture phenomenon was observed with a compressive strain exceeding 50%. For the high entropy alloys of Examples 3, 4, 5 and Comparative Example 1, the yield strength continued to increase from 818.05 to 1562MPa. The high entropy alloys of Examples 2 to 5 (except for the alloy of Comparative Example 1, which had only a strain of 31.4%) all showed high ductility and did not fracture until the engineering strain of 50%. In particular, the high entropy alloy of Example 5, compared with the high entropy alloy of Example 1, has a yield strength increased by 2.13 times, achieving a great balance between strength and toughness. Figure 6 b shows the relationship between yield strength and Al at.%. The yield strength gradually increases from Example 1 to the high entropy alloy of Comparative Example 1. In particular, the yield strength of the high entropy alloy from Example 3 to Example 4 is significantly improved (from 818.05 MPa to 1212.3 MPa).
[0036] Table 2 Room temperature mechanical properties of high entropy alloys according to the present invention
[0037]
[0038] Figure 7 The present invention's examples 1 to 5 and comparative example 1 (Fe 33 Cr 36 Ni 15 Co15 Ti1) 100-x Al x The polarization behavior in 3.5wt.% NaCl aqueous solution and the polarization behavior of 304SS. The corresponding corrosion parameters obtained from the curves are listed in Table 3, where the corrosion current density of the high entropy alloys of Examples 1 to 5 of the present invention ranges from 0.034 to 0.118 μA / cm 2 , are all less than 304 super stainless steel, self-corrosion potential -131.5~-114mV SCE , pitting potential range 451.2~953.4mV SCE , passivation range 582.7~1067.4mV SCE , which are higher than 304 super stainless steel, proving that the high entropy alloy of the present invention has excellent corrosion resistance. In addition, the curves show that all the high entropy alloys of the embodiments directly enter the passivation zone without passing through the active state, which indicates the ability to spontaneously passivate at their corresponding corrosion potentials. There is almost no current transient in the passivation zone of the high entropy alloy of the embodiment of the present invention, which indicates that it has transferable pitting corrosion ability and its pitting corrosion resistance exceeds that of 304SS.
[0039] Table 3 Comparison of electrochemical parameters of high entropy alloy and 304 super stainless steel obtained by potential polarization in NaCl solution
[0040]
[0041] The data in Table 3 were measured at room temperature, and the concentration of NaCl solution was 3.5wt.%.
[0042] Figure 8 The PD test (current density is limited to 1 mA cm) of representative alloys such as Example 1, Example 2 and Comparative Example 1 is described. -2 ) after corrosion. Figure 8 As shown in Fig. 1, there is no obvious corrosion pit in the alloy of Example 1, which confirms its good corrosion resistance. This indicates that the alloy of Example 1 may have undergone a transpassivation process because the Cr content between the FCC and Sigma phases is very high. Figure 8 b shows the corrosion morphology of the alloy of Example 2. A large number of pits are observed in the chromium-depleted FCC phase (relative to the BCC phase), indicating that for the FCC+BCC structure, localized corrosion preferentially initiates in the FCC phase. Figure 8 c is the corrosion morphology of the high entropy alloy of comparative example 1, and it can be clearly found that the alloy has undergone a large range of pitting corrosion.
[0043] Fig. 9The EIS impedance test of all embodiments and comparative examples of the high entropy alloys of the present invention is shown in Figure 1. It can be found that the radius of the capacitor decreases with the increase of Al content, indicating that the corrosion resistance gradually deteriorates. As shown in the corresponding Bode diagram ( Fig. 9 As shown in b), with the increase of Alat.%, the |Z| value of the example alloys shows a downward trend, but the |Z| values of all example high entropy alloys are higher than that of 304SS.
[0044] The present invention discloses a Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and strong plasticity matching and a preparation method thereof. The chemical expression of the high entropy alloy should be calculated as (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100-x Al x , where 0≤x≤7. The phase composition of the high entropy alloy of the present invention can change with the increase of Al content, gradually from FCC+Sigma to FCC+BCC, and then transformed into a combination of FCC+BCC+Sigma. The composition of different phases makes the yield strength of the high entropy alloy of the present invention reach up to 1315.3MPa, and the ultimate strength exceeds 3000MPa. At the same time, the compressive strain of all high entropy alloys exceeds 45% and even no fracture occurs. In addition, the corrosion current density range of the high entropy alloy of the present invention is 0.034~0.118μA / cm 2 , are all less than 304 super stainless steel, self-corrosion potential -131.5~-114mV SCE , pitting potential range 451.2~953.4mV SCE , passivation range 582.7~1067.4mV SCE , are higher than 304 super stainless steel, and the high entropy alloy disclosed in the present invention exhibits better corrosion resistance than 304SS. The high entropy alloy of the present invention can be obtained by vacuum arc melting method, and the preparation method is simple.
Claims
1. A Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and matched strength and plasticity, characterized in that: The chemical formula of the high entropy alloy is: (Fe 33 Cr 36 Ni 15 Co 15 Ti1) 100−x Al x , where 0≤x≤7.5; The phase composition of this high entropy alloy changes with the increase of Al content. When the Al content is 0, the phase composition is FCC+Sigma; in the process of Al content increasing from 0 to 3at.%, the Sigma phase gradually transforms into the BCC phase; when the Al content reaches 3at.%, all the Sigma phases are transformed into BCC, and the phase composition is FCC+BCC; when the Al content increases from 3at.% to 7at.%, that is, 3<x<7, the phase composition is FCC+BCC; when the Al content is 7at.%, the Sigma phase appears, and the phase composition is FCC+BCC+Sigma; when the Al content gradually increases from 7at.%, that is, 7<x≤7.5, the phase composition is FCC+BCC+Sigma, but the Sigma phase gradually increases and the FCC gradually decreases; when 5≤x≤7.5, the B2 phase appears.
2. The Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and matching strength and plasticity according to claim 1, characterized in that: In the chemical expression of the high entropy alloy, 2.5≤x≤7.
5.
3. The Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and matching strength and plasticity according to claim 1, characterized in that: The corrosion current density of the high entropy alloy ranges from 0.034 to 0.118 μA / cm 2 ; Self-corrosion potential -131.5~ -114 mV SCE , pitting potential range 451.2~953.4 mV SCE , passivation range 582.7~1067.4 mV SCE .
4. The method for preparing a Fe-Cr-Ni-Co-Ti-Al high entropy alloy with high corrosion resistance and matching strength and plasticity according to any one of claims 1 to 3, characterized in that: The method adopts a vacuum arc melting method, weighs raw materials of various elements according to the chemical composition of the high entropy alloy, and turns them over more than 5 times and then naturally solidifies to obtain an alloy ingot.
Citation Information
Patent Citations
AlCoCrFeNiTix high-entropy alloy material and method for preparing same
CN102776430A
Corrosion-resistant aluminum-transition metal system double-phase high-entropy alloy and preparation method thereof
CN112458352A